2018
DOI: 10.3168/jds.2018-14613
|View full text |Cite
|
Sign up to set email alerts
|

Effect of αS1-casein genotype on phenolic compounds and antioxidant activity in goat milk yogurt fortified with Rhus coriaria leaf powder

Abstract: The aim of this work was to evaluate the phenolic compounds and antioxidant activity of goat milk yogurt characterized by different α-casein genotypes and fortified with Rhus coriaria leaf powder. The α-casein genotype was determined by isoelectric focusing, total phenol content was determined by the Folin-Ciocalteu method, phenolic compounds were identified and quantified by HPLC-UV analysis, and antioxidant activity was measured using 2,2'-azino-bis-3-ethylbenzothiazoline-6-sulfonic acid and ferric-reducing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(35 citation statements)
references
References 67 publications
3
32
0
Order By: Relevance
“…The antioxidant capacity of the control yoghurt was attributed mainly either to the proteolytic activity of the starter culture used in the preparation of the yoghurts or to the enzyme activity during digestion, both of which result in the formation of bioactive peptides that have antioxidant activity. This behaviour is in agreement with the results reported in recent similar publications (Helal and Tagliazucchi 2018;Perna et al 2018).…”
Section: Antioxidant Activitysupporting
confidence: 94%
See 1 more Smart Citation
“…The antioxidant capacity of the control yoghurt was attributed mainly either to the proteolytic activity of the starter culture used in the preparation of the yoghurts or to the enzyme activity during digestion, both of which result in the formation of bioactive peptides that have antioxidant activity. This behaviour is in agreement with the results reported in recent similar publications (Helal and Tagliazucchi 2018;Perna et al 2018).…”
Section: Antioxidant Activitysupporting
confidence: 94%
“…This behaviour is in agreement with the results reported in recent similar publications (Helal and Tagliazucchi ; Perna et al . ).…”
Section: Resultsmentioning
confidence: 97%
“…Epicarbs extract showed interesting DPPH radical scavenging properties (IC 50 DPPH 0.02±0.01 mg/mL). Recently, it has been reported that R. coriaria fortified yogurt showed a significant increase in total phenolic content and antioxidant activity compared to plain yogurt …”
Section: Bioactivity Studiesmentioning
confidence: 99%
“…Accordingly, plant extracts showing good antioxidant activity may exhibit anti‐inflammatory properties. R. coriaria fruit extracts have shown interesting antioxidant properties that were mainly attributed to the presence of high concentration levels of phenolics and flavonoid compounds like gallic acid, quercetin and kaempferol . The extracts were also investigated for their anti‐inflammatory properties.…”
Section: Bioactivity Studiesmentioning
confidence: 99%
“…The antioxidant beneficial effect of sumac has been demonstrated in rabbits (Capcarova et al, ). When compared to plain yogurt, sumac‐fortified yogurt showed a more significant increase in total phenolic compounds and antioxidant activity (Perna, Simonetti, Grassi, & Gambacorta, ). Sumac extracts prevent skeletal muscle atrophy by reducing oxidative stress via catalase and superoxide dismutase II dependent mechanisms (Najjar et al, ).…”
Section: Discussionmentioning
confidence: 99%